Universities, NGOs, and civil society sustainability: preliminary lessons from Ecuador. Issue 4 (19th May 2017) - Appe, Susan; Barragán, Daniel
ABSTRACT: The context for NGOs in the Global South – delegitimising discourse, restrictive policies, and decreasing international funding – leads to major concerns about the sustainability of organised civil society. As a result, NGOs are exploring new means to contribute to social development. This article explores developing university–NGO collaborations through the case of Ecuador. It contributes to development research on two fronts. First, it examines the role of the university in the South and their collaborations with NGOs. Second, it situates university–NGO collaborations within concerns about civil society sustainability. The article presents lessons learnt by Ecuadorian NGOs.